ONE MY SCALE SUBSIDENCE OF CARBONATE SEDIMENTARY BODIES AND THE VISCOSITY OF THE LOWER CRUST - Allemand P.; Dromart G.; Garcia J.-P.; Gaumet F.; Robin C. (My University, 2004)
The possibility of flow of the lower crust under the load produced by carbonate sedimentary accumulations is investigated through the example of the Paris basin during the Middle Jurassic (i.e. Bathonian). Depositional geometries, water depths and sedimentary environments have been estimated and correlated for 164 sites spread over a surface of 380 per 220 km for three successive periods lasting each less than 0.8 My. A signal of relative vertical displacement has been extracted from water-depth and sedimentary thickness. Data have then been interpolated to produce maps of velocity of vertical displacement, sedimentation rate, water depth, and water-depth variation between two periods. The maps show that the western part of the basin is affected by faults which are independent of the sedimentation. The eastern part of the basin consists of a shallow carbonate platform affected by diffuse subsidence patches which are positively correlated with sedimentation. The patches of diffuse subsidence are elliptic in shape, with a radius of 20 km, a mean thickness of 40 m, and a maximum elevation of 10 m above the surrounding sea bottom. We suggest that the load of these patches induces the flow of the lower crust. The topography produced by these patches would be maintained at steady state by in situ carbonate production/accumulation combined with the lower crust flow. This model is tested by estimating the viscosity and the thickness of the flowing crust necessary to meet the geometric and kinematic conditions obtained from the patches. This model is valid for a lower crust viscosity of around 1021 Pa s. This value is higher by one order of magnitude than those inferred from other contexts but can be explained by the influence on viscosity of the load and temperature for a non-newtonian rock rheology.